Evapotranspiration: Potential or Reference? - Suat Irmak; Dorota Z. Haman (EDIS)
The objective of this article is to define two commonly used evapotranspiration (ET) concepts: potential evapotranspiration (ETp) and reference evapotranspiration (ETo); and to provide insight on the differences between the two terms. A common understanding of these widely used concepts in agricultural communities will help to make communication easier between farmers/growers, extension agents, and researchers in the academic environment. This document is ABE 343, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: June 2003.